A Comparative Study of Factors Influencing Purchasing Decisions at D-Mart and Metro in Vijayawada City. - Satish Kumar, D.; Bindu, P.; S. Rao, D.; Anusha, S.; Srinivas, J. (International Journal of Engineering and Technology, 2018)
Corporate retail stores are today the focal points for purchasing decisions of middle and high-income groups in urban India. However, each corporate retail store has its own model of retailing. Storing different varieties of products at same locality, location advantage, self-servicing outlets, window shopping, large scale discount, specialty stores are some of the models retailing stores have adopted. But all these retail models are not being   popular among the consumers. Consumer’s preferences and choices are varying across different retail models. In this context the present study wants to explore significant difference among corporate retail stores in Vijayawada in consumer preference and choices.